Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter R - Review of Basic Concepts - R.6 Rational Exponents - R.6 Exercises - Page 64: 88



Work Step by Step

RECALL: $(a-b)(a+b)=a^2-b^2$ Use the formula above with $a=p^{1/2}$ and $b=p^{-1/2}$ to obtain : $=(p^{1/2})^2 - (p^{-1/2})^2$ Use the rule $(a^m)^n=a^{mn}$ to obtain: $=p^{(1/2)(2)} - p^{(-1/2)(2)} \\=p^1 - p^{-1}$ Use the rule $a^{-m} = \dfrac{1}{a^m}$ to obtain: $=p-\dfrac{1}{p^1} \\=\color{blue}{p-\dfrac{1}{p}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.